Competência informacional (CoInfo): mapeamento do uso de fontes de informação por docentes e discentes da área da saúde - Oliveira, Daianny Seoni de [UNIFESP] (2015)
Constant changes resulting from the use of technology and communication, the access to information requires the use of strategies in certain contexts in order to locate it efficiently. The information literacy comes from a concern for research and training in the use of technologies by future professionals. In health, the use of scientific information based decision making, because the search results can potentially turn out to be transformed into action. The research proposes, as a general goal, to map information literacy of students from the health area in the use of sources of information for purposes of scientific research, based on information literacy standards for higher education of the Association of College and Research Libraries - ACRL .The specific goals, intended to: identify the process of search and use of information of the students (of all periods) of the courses of Health Institute and Society at UNIFESP/BS; compare performance to the standards one (1) to five (5) of the ACRL; identify the teacher's knowledge of the Health of Institute courses and Society at UNIFESP/BS courses by topic information literacy; and verify that the goal of the Pedagogical Political Project (PPP) of the Health Institute and Society at UNIFESP/BS, which aims to train professionals with extensive scientific training, has been fulfilled in the development of information literacy of students. Research it is a cross-sectional descriptive study, quantitative and qualitative approach. It was approved by the CEP/UNIFESP (655903/2014). Data collection was through semi-structured questionnaire Survey type, prepared based on information literacy standards for higher education of the Association of College and Research Libraries - ACRL. The sample consisted of 318 undergraduate students and 38 teachers of the Health Institute and Society at UNIFESP/BS undergraduate courses in Physical Education - Health mode, Physiotherapy, Nutrition, Occupational Therapy, Psychology and Social Work. It was found in relation to teachers, that: a majority indicate sources of information and use technologies for teaching but do not consider sufficient training in research and the use of these technologies by the graduates. The concept of information literacy is still little known. Regarding the students, it identified difficulties in establishing the need for information, little knowledge with respect to access the databases, difficulties in assessing the quality of information sources used need to discuss the ethical use of information and lack of knowledge the concept of information literacy. By identifying the informational profile of graduates, have been proposed guidelines for the preparation of the information literacy program in the libraries of UNIFESP/BS. The benefits of studying the information literacy are many, international studies is proving that the use of information literacy programs in universities, with the participation of librarians and teachers, have been instrumental in the training of students in the effective use of information.